(untitled) (Scientific journal of the Fergana State University, 2025)
This research is dedicated to studying the pedagogical-psychological and social characteristics of developing logical thinking in visually impaired students. The study analyzes the problems encountered in the education of visually impaired children and ways to overcome them. The role of teachers in developing students’ logical thinking, the importance of psychological support, and special teaching methods are emphasized. Additionally, social factors, including family environment and social interaction styles, are examined in relation to their impact on the overall development of visually impaired students. The results of the study will assist teachers and parents in developing effective approaches to enhance logical thinking in visually impaired students.